National Innovation System and Disruptive Innovations in Synthetic Rubber and Tire Technology - Ray R. Gehani (Journal of Technology Management & Innovation, 2008)
The current models of National Innovation Systems (NIS) are based on interactions and learning across three institutions: government, university and industry. This empirical study of the evolution of innovations in rubber and tire technologies such as the collaborative innovative suppliers (of raw materials and human capital) and disruptive rival innovators to the traditional tri-helical model of National Innovation System. This was empirically examined for the evolution of rubber and tire technology and the rise and decline of its innovative region: the Rubber Capital of the World in Akron, Ohio.